2018
DOI: 10.18203/2394-6040.ijcmph20181735
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practices regarding food hygiene and health profile of food handlers in eateries in a town in Southern Karnataka

Abstract: Background: A food handler is anyone who works in a food business and handles food, or surfaces that are likely to come into contact with food. The chance of food becoming contaminated depends largely on the health status and knowledge and practices of food safety of food handlers. Current statistics on food borne illnesses in various industrialized countries show that up to 30% of cases may be caused by poor food handling techniques, and by contaminated food served in food service establishments.Methods: A cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…We found that more than 90% of college students have the potential to follow recommended food safety practices. However, more than 82% of college students reported eating potentially dangerous foods; this finding was agreed upon by George et al (2018) and Iwu et al, (2017). Furthermore, this study shows that perceptions of food hygiene do not directly improve eating habits, especially the prohibition of consuming harmful foods.…”
Section: Practices In Personal Hygienementioning
confidence: 56%
See 3 more Smart Citations
“…We found that more than 90% of college students have the potential to follow recommended food safety practices. However, more than 82% of college students reported eating potentially dangerous foods; this finding was agreed upon by George et al (2018) and Iwu et al, (2017). Furthermore, this study shows that perceptions of food hygiene do not directly improve eating habits, especially the prohibition of consuming harmful foods.…”
Section: Practices In Personal Hygienementioning
confidence: 56%
“…Since history first recorded, the social health problem was unsafe food and water, and society faced food safety problems. However, foodborne illnesses are frequently, not apprehend as a significant health problem by people and even considered a common consequence (George et al, 2018). People perception of food safety is reportedly associated with demography.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that inadequate food hygiene knowledge and practices of kitchen personnel are a major problem in terms of public health and this situation should be prevented 20 . In another study conducted to determine the food safety knowledge levels of the kitchen personnel, 67,9% stated that they were very interested in food safety, 28,6% were interested in them, 2,1% were less interested in them and 1,3% were not interested at all.…”
Section: Discussionmentioning
confidence: 99%